PENGARUH PEMBELAJARAN PROYEK TERHADAP KEMAMPUAN MENULIS KREATIF PUISI SATIRE SISWA KELAS X MAN PURWOREJO - Adelya Indradini, Alda; Sholeh, Khabib; Daru Santoso, Suryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the challenges in creative writing instruction, specifically the low ability of students to process vocabulary and language structures, a lack of critical social awareness, and the prevalence of conventional teacher-centered methods that limit active student engagement. The objective of this research is to examine the differences in creative satire poetry writing abilities between students taught using the Project-Based Learning (PjBL) model and those taught using conventional methods, as well as to measure the overall effectiveness of the PjBL model. Utilizing a quantitative approach with a Posttest-Only Control Group Design, this study involved 66 tenth-grade students from MAN Purworejo during the 2025/2026 academic year, divided equally into an experimental group (33 students) and a control group (33 students). Data were gathered through a post-test writing performance instrument evaluated with a validated rubric and analyzed using the Independent Samples T-Test and Cohen’s d effect size formula. The results indicated a statistically significant difference in creative writing performance between the two groups (p = 0.000 < 0.05). The experimental group achieved a significantly higher mean score (86.00) compared to the control group (75.94). Furthermore, the effect size analysis revealed a Cohen’s d coefficient of 1.48, demonstrating that the implementation of Project-Based Learning has a very large positive effect on students’ ability to write creative satire poetry. In conclusion, PjBL serves as a highly effective and innovative instructional model that enhances both high-order thinking and creative writing competencies in secondary language education.